2018
DOI: 10.1016/j.jplph.2018.08.003
|View full text |Cite
|
Sign up to set email alerts
|

Nitrate- and nitric oxide-induced plant growth in pea seedlings is linked to antioxidative metabolism and the ABA/GA balance

Abstract: This study looks at the effects of potassium nitrate (KNO) and sodium nitroprusside (SNP), a nitric oxide (NO)-donor, on the development, antioxidant defences and on the abscisic acid (ABA) and gibberellin (GA) levels in pea seedlings. Results show that 10 mM KNO and 50 μM SNP stimulate seedling fresh weight (FW), although this effect is not reverted by the action of 2-4-carboxyphenyl-4,4,5,5-tetramethylimidazoline-1-oxyl-3-oxide (cPTIO), a NO-scavenger. The KNO treatment increased peroxidase (POX) and ascorba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
29
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 28 publications
(35 citation statements)
references
References 45 publications
3
29
3
Order By: Relevance
“…Potassium nitrate (KNO 3 ) has been demonstrated to break seed dormancy, promote seed germination and enhance growth uniformity in a variety of plant species, including tomato, maize, Arabidopsis and pea [9][10][11][12]. However, the mechanism by which KNO 3 improves seed germination and seedling establishment remains unclear.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Potassium nitrate (KNO 3 ) has been demonstrated to break seed dormancy, promote seed germination and enhance growth uniformity in a variety of plant species, including tomato, maize, Arabidopsis and pea [9][10][11][12]. However, the mechanism by which KNO 3 improves seed germination and seedling establishment remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Lincoln) displayed reduced germination and seedling growth when incubated for three days in the presence of 30 or 40 mM KNO 3 , whereas 10 mM KNO 3 stimulated early seedling growth. However, when the pea seeds were imbibed with KNO 3 (40 mM) for 24 h and then incubated in distilled water, seedling fresh weight was enhanced, whereas germination rate remained Seeds 2021, 1 6 unchanged [12]. Other authors [14] suggested that nitrates may enhance seed germination and early seedling growth due to the dual role of N as a plant essential element for growth and as a signalling molecule.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, it has been reported that melon plants treated with blue light or the combination red-blue light (3:1) increased the tolerance to powdery mildew, whereas the combination red-blue light increased plant growth [23]. Regarding pea seeds, recent works described that H 2 O 2 -priming increased the germination rate as well as the early seedling growth [10], whereas KNO 3 treatments modulated the levels of the plant hormones GA 4 and ABA, this response being correlated with an increase in the biomass of pea seedlings [24].…”
Section: Introductionmentioning
confidence: 99%
“…Both KNO 3 and sodium nitroprusside (SNP), a nitric oxide (NO)-donor, stimulated early seedling growth. Both treatments reduced ABA concentrations and induced the GA 4 levels in pea seedlings, thus resulting in a strong decrease in the ABA/GA ratio [12].…”
mentioning
confidence: 98%
“…ROSs, such as nitric oxide (NO), in addition to different nitrogen-containing compounds, including nitrite, nitrate and sodium nitroprusside (SNP, a NO-generating compound), have also been associated with seed dormancy breaking and the germination process [4,11,12]. Both KNO 3 and sodium nitroprusside (SNP), a nitric oxide (NO)-donor, stimulated early seedling growth.…”
mentioning
confidence: 99%